Faculty behaviors related to effective facilitation of small group discussions in problem based learning setting - Montoya, Melfer R.
Expert handling of small group discussions of first year students by facilitators of Cebu Institute of Medicine allows students to learn in an engaging and stimulating atmosphere. This environment will permit them to develop self directed learning skills and critical thinking. The objectives of this study are to (1) Describe faculty behaviors while facilitating small group discussions in a problem based learning setting in terms of managing content and group dynamics; (2) Determine whether facilitating behaviors vary according to basic biomedical proficiency, academic rank and years of teaching experience; and (3) Determine correlation between faculty behaviors and overall effectiveness rating as facilitators. This is a cross sectional survey involving all facilitators who are assigned in the Basic Biomedical Science of the first year level. The facilitating behaviors that were evaluated were those that relate to subject matter knowledge namely, use of expertise, cognitive congruence and test orientation and behaviors that relate to process facilitation skills, namely, authority, role congruence and cooperation orientation. These facilitating behaviors were also assessed in terms of relating them to overall effectiveness using a rating scale. Statistical analysis with a level of significance set at .05 was done through t-test and analysis of variance using the Statistical Package for the Social Sciences version 14. This study shows that all facilitators in the first year level have the facilitating behaviors that relate to effectiveness in facilitating. Tests to determine if there was a significant difference in their facilitating behaviors due to basic biomedical proficiency, academic rank and years of teaching experience showed facilitating behaviors that were consistently ranked as first and second. These facilitating behaviors are use of expertise and cooperation orientation. Facilitating behaviors are use of expertise and cooperation orientation. Facilitators with disciplinary training scored higher in use of expertise and cooperation orientation. Facilitators with disciplinary training scored higher in use of expertise (UE), cooperation orientation (CC), role congruence (RC), authority (AU) and cooperation orientation (CO) compared to those without disciplinary training. Despite variations due to basic biomedical proficiency, different academic ranks and different years of teaching experience, majority of students agreed, that the use of expertise (UE) by facilitators correlates strongly with overall effectiveness rating. It is recommended that this study be also done in the last 3 months of the school year of the first year as well as in the second year level. Data can be used as basis for future faculty selection, training and evaluation.